Penerapan Green Human Resource Management (GHRM) Dalam Menciptakan Inovasi Produk Dan Proses pada Industri Kecil Menengah Kopi di Indonesia - I Ketut Pasek; Ni Putu Maha Lina; I Wayan Siwantara; Ni Wayan Sumetri; I Wayan Sukarta (Jurnal Bisnis dan Kewirausahaan, 2022)
The study aims at analyzing the direct and indirect effects of green human resources management, innovative work behaviour, knowledge inertia, and innovation of the coffee small medium entreprises (SMEs) in Bali. This study was conducted based on gaps in previous studies, namely: First, the limitations of research that discusses the study of process innovation compared to research that discusses product innovation. Second, the lack of studies that can enrich the implementation of GHRM at the micro level. Third, the lack of studies that can identify the factors forming a more comprehensive model of process innovation. Respondents were 284 Coffee SMEs in Bali. Data were collected by using quetionnaire. Path analysis is used in the Structural Equation Modeling (SEM) equation with the help of SmartPLS. The results showed that: 1) Green human resources management has a possitive effect on innovation, 2) Green human resources management has a possitive effect on innovative work behavior, 3) innovative work behavior has a positive effect on innovation, 4) Innovative work behavior partially mediates the relationship between GHRM and innovation, 5) Knowledge inertia has no significant effect in moderating green human resource management (GHRM) to innovative work behavior.